Development of Roulette Spin Media on al-Islam Subjects - Nurwindi Maghfiroh Sehat; Moch. Charis Hidayat; Hayumuti (NAJAHA, 2025)
The purpose of this research is to determine the validity level of the product in the form of roulette spin learning media that the researcher has made. This research is focused on developing learning media that can attract students' interest in learning, especially in Al-Islam subjects. Learning media can later be used by teachers and students. And helps in communication between teachers and students. This rosette uses the R&D (research and development) research method with a 4D development model namely Define, Design, Development, and Disseminate, but researchers only limit it to the Development stage. The test results obtained are as follows: 1) the material validation test obtains a percentage value of 87% with very high score criteria. 2) the media validation test gets a percentage value of 77.5% with a high score criterion. and 3) student response tests to the roulette spin learning media obtained a percentage value of 86% with very high criteria. Based on the results of the material validation test, media validation, and student responses to the spin roulette learning media for class VIII semester 2 fasting material is feasible to use.